2011
DOI: 10.1111/j.1365-2125.2010.03873.x
|View full text |Cite
|
Sign up to set email alerts
|

Relative bioavailability of terbutaline to the lung following inhalation, using urinary excretion

Abstract: WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT• The relative bioavailability of salbutamol to the lung and body following inhalation can be identified by a urinary pharmacokinetic method. WHAT THIS STUDY ADDS• The amount of terbutaline excreted in the urine during the first 30 min and over the 24 h period post inhalation represents the relative bioavailability of terbutaline to the lung and the body following an inhalation.• Terbutaline study doses can replace a routine salbutamol dose during studies in patients whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 7 publications
(12 reference statements)
1
40
0
Order By: Relevance
“…The 30 min urinary excretion highlights the usefulness of this index as a measure of the relative bioavailability of beclometasone dipropionate to the lungs following an inhalation. The inter‐ and the intra‐individual variation is consistent with that previously reported for salbutamol [16], as well as gentamicin [19], formoterol [20], sodium cromoglicate [21] and terbutaline [22].…”
Section: Discussionsupporting
confidence: 90%
“…The 30 min urinary excretion highlights the usefulness of this index as a measure of the relative bioavailability of beclometasone dipropionate to the lungs following an inhalation. The inter‐ and the intra‐individual variation is consistent with that previously reported for salbutamol [16], as well as gentamicin [19], formoterol [20], sodium cromoglicate [21] and terbutaline [22].…”
Section: Discussionsupporting
confidence: 90%
“…A novel pharmacokinetic method that have been previously developed for Salbutamol 7 and validated for terbutaline 8 was used here to compare the different inhalation maneuvers. As mentioned before, the previously validated terbutaline pharmacokinetic method had shown that the amount of terbutaline excreted in urine 30 min post dosing is an index of the amount of terbutaline deposited in the The amount excreted 30 min and 24 h post dosing using slow and fast inhalation flows after one inhalation from healthy subject and COPD patients confirm the flow dependent dose emission property of the Turbuhaler.…”
Section: Discussionmentioning
confidence: 99%
“…On each study day subjects were allowed to have a light breakfast and no caffeine or alcohol containing drinks for at least 12 hbefore dosing. According to the novel urinary terbutaline method, 8 immediately before each study dose each subject voided their urine then provided a urine sample 30 min after the start of the first dose and cumulatively collected their urine for 24 h. The volumes of urine samples were measured and assayed for the urinary terbutaline concentration using an HPLC-fluorescence spectrophotometry. The terbutaline was extracted from the urine samples together with Bamethane (Sigma, UK) as internal standard using solid phase extraction, Isolute HCX 130 mg 10 ml XL cartridge and Oasis HLB 30 mg cartridge, then injected in the HPLC system.…”
Section: In Vivo Proceduresmentioning
confidence: 99%
“…The output property Y1 was the percentage of excreted dose (lung or systemic bioavailability) 6,17 . Sampling time of 0.5 hour was indicative of lung bioavailability of the inhaled drug, while 24 hour cumulative samples were representative of the amount of the systemic bioavailability of the drug 25 …”
Section: Methodsmentioning
confidence: 99%